Dividing and setting strategy of improving calculation efficiency for needle electrode corona discharge with a large‐scale space. (22nd November 2021) - Li, Dingchen; Li, Chuan; Li, Jiawei; Wang, Pengyu; Liu, Zhi; Yang, Wendi; Zhang, Ming; Yang, Yong; Yu, Kexun
Abstract: Needle electrodes are widely used in the research of corona discharge. Aiming at the problem of needle electrode discharge in a large‐scale space (tens or even hundreds of centimetres), a hybrid model was proposed in the previous work. However, its indispensable multiple iterations result in huge computation and further limit its wide applications. Therefore, a strategy to improve the computing efficiency by setting initial values in different computational domains is put forward in this work. Three types of setting initial values (global constant, partition constant and partition exponent) are simulated and compared in detail. The calculation results show that the calculation efficiency can be increased by 1.4 times simply through setting initial values of charged particles as different constants for the divided subdomains, and further be improved by 4.3 times by setting those in the ionization region as an exponential distribution. The extension of the proposed strategy has also been discussed under various voltages, which shows that the results under other voltages can be quickly obtained based on the fitted coefficients under a specific voltage, and the improvement can reach up to 10 times. The accuracy of calculated results has been demonstrated by a needle‐plate electrode device with a vertical distance of 25 cm. This research provides an effective strategy for improving the computing efficiency of corona discharge in a large‐scale space, and implies the potential in optimizing the analyses of complex electrodes.